Instructional leadership, work motivation and relations of work performance of history teachers in Sabah, Malaysia - Roslee Talip (susurgalur, 2015)
The study involved 120 teachers, who teach History in Kota Kinabalu, Sabah, Malaysia. Respondents were given a questionnaire, which consisted of three parts. Part A consisted of demographic questions. Part B consisted of 55 items that were on instructional leadership. Part C consisted of 20 items on work motivation; and Part D consisted of 30 items on teacher performance. A total of four hypotheses have been presented in this study. Data test has been measured and tested by using descriptive statistics and ANOVA (Analysis of Variance) with significance level p < 0.01. The findings of Pearson correlation analysis showed a significant relationship of instructional leadership and teacher performance in History (r = .523, sig = .000). While the findings of Pearson correlation analysis showed no significant difference of work motivation and work performance of History subject teachers (r = .172, sig = .060). In terms of implications of the study found that History teachers, who practice instructional leadership in their teaching and learning, will show a positive impact on teacher performance in History.